LAYANAN INFORMASI KARIR TEKNIK MIND MAP BERBASIS GITMIND UNTUK MENINGKATKAN KEPUTUSAN PERENCANAAN KARIR SISWA - Hijrah Eko Putro (STKIP PGRI SUMENEP, 2024)
This research was conducted with the aim of determining the effectiveness of career information with the Gitmind technique to improve career planning of students of SMP Al Iman Kota Magelang. Experimental research methods used in this study. The stage carried out is to test the effectiveness of the Gitmind technique career information service to improve students' career planning. The research design used pre-experimental: one group pretest-posttest design with purposife sampling. The results of the effectiveness test of this study are that this model is effective for improving students' career planning. The research sample used purposive sampling technique totaling 8 students. The student's career planning level has improved after following career information with the Gitmind technique. This can be seen from the career planning of students before and after being given career information with the Gitmind technique by 22% and reinforced through effectiveness tests using t-tests that show -t count (-7.869) < -t table (-2.120).